Electric‐Field‐Controlled Dopant Distribution in Organic Semiconductors. Issue 30 (6th June 2017) - Müller, Lars; Rhim, Seon‐Young; Sivanesan, Vipilan; Wang, Dongxiang; Hietzschold, Sebastian; Reiser, Patrick; Mankel, Eric; Beck, Sebastian; Barlow, Stephen; Marder, Seth R.; Pucci, Annemarie; Kowalsky, Wolfgang; et al.
Abstract : Stable electrical doping of organic semiconductors is fundamental for the functionality of high performance devices. It is known that dopants can be subjected to strong diffusion in certain organic semiconductors. This work studies the impact of operating conditions on thin films of the polymer poly(3‐hexylthiophene) (P3HT) and the small molecule Spiro‐MeOTAD, doped with two differently sized p‐type dopants. The negatively charged dopants can drift upon application of an electric field in thin films of doped P3HT over surprisingly large distances. This drift is not observed in the small molecule Spiro‐MeOTAD. Upon the dopants' directional movement in P3HT, a dedoped region forms at the negatively biased electrode, increasing the overall resistance of the thin film. In addition to electrical measurements, optical microscopy, spatially resolved infrared spectroscopy, and scanning Kelvin probe microscopy are used to investigate the drift of dopants. Dopant mobilities of 10 −9 to 10 −8 cm 2 V −1 s −1 are estimated. This drift over several micrometers is reversible and can be controlled. Furthermore, this study presents a novel memory device to illustrate the applicability of this effect. The results emphasize the importance of dynamic processes under operating conditions that must be considered even for single doped layers. Abstract : The electric‐field‐controlled movement of dopants in organic semiconductors is investigated with electrical measurements, optical microscopy, and spatially resolved infrared spectroscopy. This study evaluates two p‐type dopants in a polymer and small molecule host material and utilizes the movement to build a proof‐of‐concept memristive device by reversibly changing the overall conductivity of thin films.